Inclusion of IR-820 into Soybean-Phosphatides-Based Nanoparticles for Near-Infrared-Triggered Release and Endolysosomal Escape in HaCaT Keratinocytes at Insignificant Cytotoxic Level - Homsirikamol, Chaiyarerk (Int J Nanomedicine, 2020)
PURPOSE: The degradation of drugs within endolysosomes has been widely addressed as a cause of poor bioavailability. One of the strategies to allow molecules to escape from a destructive fate is to introduce a photosensitizing moiety into a drug carrier enabling the permeabilization of endosomes and endolysosomes upon irradiation. This paper presents an alternative delivery nanosystem composed of cost-effective soybean phosphatides mixed with IR-820, a near-infrared (NIR) sensitizer, to load various active compounds and trigger an endolysosomal escape with a low cytotoxic effect. METHODS: IR-820-incorporated phosphatides-based nanoparticles were formulated using a thin-film hydration method to encapsulate different molecular probes and a drug model. The nanoparticles were characterized in vitro using dynamic light scattering, transmission electron microscopy, as well as ultraviolet–visible and fluorescence spectroscopy techniques. The NIR-corresponding generation of the photochemical products, the content release, and the cytotoxicity toward the HaCaT keratinocyte cell line were evaluated. The cellular internalization and endolysosomal escape were monitored using a cytochemical marker and fluorescent probes with a colocalization analysis. RESULTS: The IR-820-combined nanoparticles revealed the NIR-triggered changes in the singlet oxygen presence, nanoparticle architecture, and release rate without being cytotoxic. Additionally, the nanoplatform appeared to enhance cellular uptake of the macromolecules. The localization of the cytochemical marker and the colocalization analysis on the fluorescence signals of the encapsulated fluorophore and the lysosome-labeling reporter implied the transient endolysosomal escape of the cargo within the HaCaT cells after NIR irradiation. CONCLUSION: The inclusion of IR-820 into a soybean-phosphatides base ingredient provides NIR responsiveness, particularly the endolysosomal escape of the payload, to the formulated nanoparticles, while preserving the beneficial properties as a drug carrier. This alternative delivery nanomedicine system has future potential to provide high bioavailability of cytosolic drugs utilizing time- and spatial-controllable NIR triggerability as well as the synergistic therapeutic effects with NIR-biomodulation.